Educação de Jovens e Adultos e Formação Continuada: uma análise no Centro de Ensino Cidade de São Luís, em São Luís/MA - GOMES , Elizangela Duarte (2022)
The present study is linked to the research line School, Curriculum and Teacher Training of the Graduate Program in Education at the Federal University of Maranhão – UFMA. With the theme “Youth And Adult Education And Continuing Education: an analysis at the Centro de Ensino Cidade de São Luís in São Luís/MA”, the general objective was to analyze the process of continuing education of teachers of Youth and Adult Education at the Centro de Ensino City of São Luís. The qualitative research focused on the critical perspective, in order to highlight continuing education, in the context of Youth and Adult Education offered by the aforementioned Center, considering the specificities contained in this teaching modality. Therefore, we focus on the educational reality of Maranhão, from the Centro de Ensino Cidade de São Luís, taking as a starting point, the normative framework that governs education in the country, as well as the initiatives developed in the state, their advances and their setbacks. , with a view to providing an understanding of the aspects that guide this theme from a historical perspective and its configuration in the locus of this research, through the voices of professors, who, when narrating their experiences, presented a brief overview of the materialization of training continued in the EJA. In order to discuss Youth and Adult Education, we rely on the thinking of authors such as Arroyo (2017); Carvalho (2005)Freire (1979, 1996, 2010), Di Pierro (2020), Haddad (2000), Soares (2001), the discussions on Continuing Education are anchored in the contributions of Ferreira (2014, 2017), Freitas (2002, 2003, 2014), Gatti (2008, 2016, 2020), Imberon (2006), Nóvoa (1999, 2006), Tardif (2000) methodologically we support ourselves in Bogdan, Biklen (1994), Kosik (2006), Minayo (2001) , Damasceno (2001), among other authors. The documents researched were the Federal Constitution of 1988; the Law of Guidelines and Basis for National Education, Law No. 9,394/1996; the National Education Plan (PNE), Law No. 13.005/2014, which lists continuing education as a national goal for valuing education professionals during the 2014-2024 decade, promoting training with goals No. 15 and 16 continued search for good quality education; the State Education Plan (PEE), Law No. 10,099/2014; Resolution No. 144/2006, and other documents mentioned throughout the work. The subjects of our research were six teachers, all licensed and with more than fifteen (15) years of professional experience in the EJA modality. We used as a research instrument the semi structured interview, with some teachers remotely, with others in person, respecting the sanitary protocol of social distance, required by the World Health Organization, due to the Covid 19 pandemic. that continuing education is aimed at regular education, with no specific continuing education for EJA, and it is up to the teachers to make the necessary adaptations, leaving evident in the speeches, the concern of some professionals to have specific training for the modality they work. Another important point to highlight is that all the teachers surveyed are regular teachers of the state education network, some only complete the workday at EJA. It is concluded that the specific continuing education for the EJA modality, in its own space for the training of the teacher in service, is of paramount importance for the quality of teaching, and consequently, for the success of the students.